NIR-triggering cobalt single-atom enzyme switches off-to-on for boosting the interactive dynamic effects of multimodal phototherapy - Hao Dai; Ali Han; Xijun Wang; Peng Zhu; Dingsheng Wang; Yuguang Wang (Nature Communications)
Abstract Noninvasive phototherapy with functional preservation is considered to be a promising cancer therapeutic method. However, the clinical application of tumor phototherapy is severely restrained by the lack of appropriate multimodal phototherapy agents exhibiting an ideal tissue penetration depth to maximize the antitumor efficiency as well as to maintain important tissue functions. Herein, an innovative near-infrared ray (NIR)-triggered photodynamic-photocatalytic-photothermal therapy (PDT-PCT-PTT) agent based on an atomically dispersed cobalt single-atom enzyme (Co-SAE) anchored on hollow N-doped carbon sphere (HNCS) has been strategically developed. Reactive oxygen species (ROS) are highly activated and amplified through both the photogenerated electrons and the photothermal conversion induced by NIR irradiation, as systematically demonstrated by the experimental and density functional theory (DFT) calculation results. Mild hyperthermia is eventually achieved through apoptosis and ferroptosis caused by ROS, significantly boosting the interaction of ROS dynamic effects and thermodynamic effects in the tumor microenvironment (TME). More importantly, Co-SAEs/HNCS not only causes multimodal damage through limited TME products but also preserves important organ functions by the induction of mild local hyperthermia. This work expands the biomedical application field of SAEs and presents an innovative all-in-one, multimodal concept for the noninvasive treatment of head and neck cancer.